Constitution-making and transnational legal order (Comparative Constitutional law and legal order, 2019)
Since the rise of nation -state in 19th century, constitutions have been seen as an embodiment of national velues and identity. However, individuals, ideals, institutions from abroad have always influenced constitutions, and so the process is better described as transnational. As cross-broder interaction is increasing in intensity, a dominant transnational legal order for constitutions has emerged, with its own norms, guidelines, shared ideas. This volume address the actors, networks, and process involved in conctitutions making as well as the ralted challenges from transnational and compartive perspective. Drawing from the research on transnational legal orders, this work explores and examines constitutions making in every region of the world.